2000
DOI: 10.1103/physrevb.61.5683
|View full text |Cite
|
Sign up to set email alerts
|

Electron emission and structural characterization of a rope of single-walled carbon nanotubes

Abstract: The electron emission and structural properties of an isolated ''rope'' comprised of ϳ70 individual singlewalled nanotubes ͑SWNT's͒ were investigated by measuring the field-emission energy distributions and by using field-ion microscopy ͑FIM͒. Field-emission energy distributions, obtained under ultrahigh-vacuum conditions, revealed that the emitting nanotube has a large density of states near the Fermi energy, with an energy distribution of emitted electrons close to that predicted by the free-electron theory.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
44
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(50 citation statements)
references
References 44 publications
5
44
0
1
Order By: Relevance
“…The results showed a wide spectrum of behavior, particularly in the few years following the first FE experiments of 1995. As examples, the I(V) characteristics may, more or less, follow the FN law, [19,20,23] or tend either to bend up or to saturate at high currents. [24] FE microscopy (FEM) may show complicated emission patterns, [25,26] or those that come from well-specified closed CNTs whose apexes approach ideal structures.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…The results showed a wide spectrum of behavior, particularly in the few years following the first FE experiments of 1995. As examples, the I(V) characteristics may, more or less, follow the FN law, [19,20,23] or tend either to bend up or to saturate at high currents. [24] FE microscopy (FEM) may show complicated emission patterns, [25,26] or those that come from well-specified closed CNTs whose apexes approach ideal structures.…”
Section: Introductionmentioning
confidence: 97%
“…[24] FE microscopy (FEM) may show complicated emission patterns, [25,26] or those that come from well-specified closed CNTs whose apexes approach ideal structures. [27] The total energy distributions (TEDs) may show very narrow energy spreads [19,26] and multiple peaks, [26,28] or be those that approach standard theory. [29,30] The community may have been looking for something new in FE specifically related to the novel crystalline or electronic structure of CNTs; however, views are now converging to the idea that the I(V) curves and TEDs from properly cleaned MWNTs are governed to first order by the FN theory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A proportionality constant ␤ relates the applied voltage V to the resulting electric field E by E = ␤V. Ultimately, ␤ can be related to the tip geometry ͑␥ tip ͒ and a field compress factor k, 14 using ␤ =1/ ͑k␥ tip ͒. The corresponding FowlerNordheim plot of the emitted current versus applied voltage ͓ln ͑I / V 2 ͒ versus 1/V͔ from our CNT cathode is nearly linear ͓see Fig.…”
mentioning
confidence: 95%
“…Lovall et al reported that a single nanotube protrudes from the tip of a SWNT-rope. 12 Our measurements, which provide the transport properties of a single SWNT, were made using a piezo-driven nanopositioning system at room temperature in air (Fig. 2a).…”
mentioning
confidence: 99%